Penerapan Corporate Social Responsibility pada Hotel dan Resort: Relevansinya bagi Pengembangan Rancabango Hotel & Resort - Aliya Alasri Nurrochim; Ariela Maharani Putri Bahri; Azizah Oktaviani; Andi Muhammad Yasin (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study examines the implementation of Corporate Social Responsibility at Rancabango Hotel & Resort. This study employed a qualitative approach with a library research approach. Based on the literature review on the implementation of Corporate Social Responsibility (CSR) in the hotel and resort industry, it can be concluded that CSR is a concept that requires companies to focus not only on profit but also on the social, environmental, economic, and cultural impacts of their operational activities. CSR models such as Carroll's Pyramid, Triple Bottom Line, and Stakeholder Theory provide a conceptual framework that helps hotels design sustainable and responsible programs. CSR is not only a moral obligation but also a strategic component that can support the long-term sustainability and competitiveness of Rancabango Hotel & Resort.